2003
DOI: 10.1002/ejoc.200300071
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Annulation of Aryl‐1,2‐diols and Propargylic Carbonates. Theoretical Study of the Observed Regioselectivities

Abstract: Methyl 1-methylprop-2-ynyl carbonate reacts with 3-and 4-substituted benzene-1,2-diols to give 2,3-dihydro-3-methyl-2-methylidene-1,4-benzodioxines, as a mixture of regioisomers in the case of methoxy-substituted diphenol, and a single regioisomer for the nitro-and the formyl-substituted diphenols. The oxyanion which attacks first corresponds to the less acidic hydroxy function, and the attack of the second oxyanion on the η 3 -allylpalladium intermediate is directed toward the more substituted carbon atom. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…A similar DFT study of [(PH 3 ) 2 Pd(η 3 -CH 3 CHCCH)] + was performed by Delbecq, Sinou, and co-workers . Similar to the results reported here for a rhenium cation, they found that the central propargylic carbon was most positive, that the LUMO had a node at the central carbon, and that nucleophilic attack at the central carbon involved interaction with LUMO+1.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar DFT study of [(PH 3 ) 2 Pd(η 3 -CH 3 CHCCH)] + was performed by Delbecq, Sinou, and co-workers . Similar to the results reported here for a rhenium cation, they found that the central propargylic carbon was most positive, that the LUMO had a node at the central carbon, and that nucleophilic attack at the central carbon involved interaction with LUMO+1.…”
Section: Discussionsupporting
confidence: 83%
“…A similar DFT study of [(PH 3 ) 2 Pd(η 3 -CH 3 CHCtCH)] + was performed by Delbecq, Sinou, and co-workers. 37 Similar to the results reported here for a rhenium cation, they found that the central propargylic carbon was most positive, that the LUMO had a node at the central carbon, and that nucleophilic attack at the central carbon involved interaction with LUMO+1. Their conclusion that regioselective attack at the central carbon resulted from a combination of charge control and the availability of a low-lying orbital centered on the middle propargylic carbon is similar to that reported here.…”
Section: Discussionsupporting
confidence: 78%
“…Initially, regio- and stereoselective S N 2′ attack of palladium(0) to propargylic compounds proceeds to yield the allenylpalladium intermediate A . First cyclization by the hydroxy group on the central carbon of π-propargylpalladium complex B , which is formed by rearrangement of A , would generate a fused palladacyclobutene intermediate C . This is followed by protonation to form complex D without loss of chirality.…”
Section: Resultsmentioning
confidence: 99%
“…This heteroannulation was extended to substituted catechols (Scheme 19) [45]. Methyl 1-methylpro-2-ynyl carbonate reacted with 3-methoxybenzene-1,2-diol to afford the two regioisomers 52a and 53a in a 1:1 ratio, while the condensation with 2,3-dihydroxybenzaldehyde or 3-nitrobenzene-1,2-diol gave a unique regioisomer 52b and 52c in 96 and 85% yields.…”
Section: Palladium(0)-catalysismentioning
confidence: 99%